A simple particle–spring method for capturing the continuous–discontinuous processes of brittle materials. (June 2022) - Feng, Chun; Liu, Xinming; Lin, Qindong; Li, Shihai
Abstract: Comparing to the continuum-based method such as the finite element method (FEM), particle–spring method can relatively easily simulate the cracking processes of brittle materials such as rocks by deactivating or adjusting springs/contacts. However, it is still challenging for building the equivalence between particle–spring system and the original continuous media, then capturing the whole continuous–discontinuous processes. In this work, a simple particle–spring system is proposed in which different types of springs are introduced including normal, tangential, pure shearing and Poisson's springs. The stiffness of the springs are obtained by bridging the proposed model and triangular FEM element. Moreover, novel mixed type failure criteria for the breakage of the springs are also provided. By numerical studies the reliability and robustness of the model are proven which gives comparable results to the conventional FEM model. With the new model, progressive failure processes of rock-like material can be properly captured.